The Large Seed Size of Domesticated Lima Beans Mitigates Intraspecific Competition among Seed Beetle Larvae - Cuny, Maximilien A. C.; Shlichta, Gwen J.; Benrey, Betty (Frontiers in Ecology and Evolution, 2017)
The domestication of beans has selected for larger seeds in cultivated plants compared to their wild relatives. This has not only resulted in an enhanced resource for humans, but also for the insects that feed on these seeds. Seed beetles that attack wild and cultivated seeds often lay several eggs on a single seed. We hypothesized that the larger seed size of domesticated beans will mitigate the competition among the larvae that hatch from these eggs, with important implications for their growth and survival. To test this we examined how seed size of wild and cultivated Phaseolus lunatus (lima bean) affect the performance of the Mexican bean weevil Zabrotes subfasciatus, an important pest of beans in Mexico. A negative correlation was found between the initial number of eggs on a seed and the weight of female beetles that emerged, but only for the much smaller wild seeds. Similarly, beetle survival was found to be negatively correlated with competition intensity only on wild seeds. Our results imply that by selecting for larger seeds, domestication of Phaseolus lunatus has reduced the intensity of intraspecific larval competition of Z. subfasciatus.